Preparing for leadership : what it takes to take the lead - Dennis, Donna J.; Meola, Deborah Dennis (AMACOM/American Management Association, 2009)
What makes a great leader' Confidence' Trust' Vision' The ability to inspire' The answer is complex yet understandable. The good news is that most great leaders are made, not born, and many of the characteristics associated with effective leadership can be assessed, trained, and developed. Based on the best-selling seminar by the American Management Association, this book gives readers practical advice on how they can:- get noticed by learning how to look and talk like a leader- become expert teambuilders, coaches, and communicators- gain and use power and influence positively- guard against the pitfalls of intraorganizational politics- identify and build strategic alliances- elicit support- motivate othersContaining practical tools including assessments, tips, and checklists, this book shows readers how to take their organizations into the future, inspire those around them ... and achieve beyond what is expected.